How Anticipated Emotions Guide Self-Control Judgments - Kotabe, Hiroki P.; Righetti, Francesca; Hofmann, Wilhelm (Frontiers in Psychology, 2019)
When considering whether to enact or not to enact a tempting option, people often anticipate how their choices will make them feel, typically resulting in a “mixed bag” of conflicting emotions. Building on earlier work, we propose an integrative theoretical model of this judgment process and empirically test its main propositions using a novel procedure to capture and integrate both the intensity and duration of anticipated emotions. We identify and theoretically integrate four highly relevant key emotions, pleasure, frustration, guilt, and pride. Whereas the former two (basic hedonic) emotions are anticipated to dissipate relatively quickly, the latter two (self-conscious) emotions are anticipated to be more long-lived. Regarding the relative weighting of emotions, we obtained evidence for a relative guilt bias and pride neglect under default conditions. Furthermore, we identify situational influences on this judgment process and find that rendering self-conscious emotions more situationally salient positively impacts self-control decision-making. We discuss how these findings build on an integrative theory of self-control and how they are useful for the design of choice environments and interventions.